مطبوعة بيداغوجية المقاولاتية موجه لطلبة السنة الثاتية ماستر تخصص علم الاجتماع التربية - عــمر, بوســــكرة (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
This pedagogical publication on the scale of the sociology of the educational institution, directed to first-year master’s students in the sociology of education, includes a group of lectures that aim to enable the student to understand the various educational applications of social theories that dealt with the educational institution as a social system that interacts with the rest of the systems and is affected in its function and structure by the changes that occur to it. Because the educational institution is that social structure that derives its status from the various social roles that it performs, as these roles are characterized by integration and support with each other to achieve a major goal that society desires and seeks to achieve, and the position of the educational institution in society is strengthened more and more through its outputs represented by the individuals it produces. According to their competence, the institution will be rewarded or reprimanded. تتضمن هذه المطبوعة البيداغوجية الخاصة بمقياس المقاولاتيةوالموجهة لطلبة السنة الثانيةماستر في علم الاجتماع التربية مجموعة من المحاضرات التي تهدف لتمكين الطالب من فهم مختلف المفاهيم والمصطلحات المتعلقة بالمقاولاتيةباعتبارها مهنة تشمل إدارة وتنفيذ الأعمال الإنشائية والتشييدية. حيث يقوم المقاول بتنفيذ المشاريع العمرانية والبنية التحتية مثل الأبنية والطرق والمدارس والمستشفيات. وعليه يجب أن يكون لدى المقاول مهارات تنظيمية جيدة في إدارة المشروع وتخطيط العمل وتنسيق فريق العمل. بحيث يعمل على توفير الموارد اللازمة وإدارة العمال لضمان تنفيذ المشروع بشكل متقن وفقا للمواصفات والمعايير المطلوبة. تتطلب المقاولاتية الالتزام بالجودة والسلامة والتكلفة المحددة ليحقق المقاول النجاح في مجاله.
Keywords: المقاول، المشروع، المقاولة، المقاولاتية. Contractor, project, contracting, contracting